nataliekedwards04
nataliekedwards04
04-09-2020
Mathematics
contestada
Solve 3(2 – c) = – (c + 4).
Respuesta :
muhammadolim
muhammadolim
04-09-2020
Answer:
c = 5
Step-by-step explanation:
[tex]3(2-c) = -(c+4)[/tex]
[tex]3\times 2-3\times c=-c-4[/tex]
[tex]6-3c=-c-4[/tex]
[tex]c-3c=-4-6[/tex]
[tex]-2c=-10[/tex]
[tex]c=5[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 93+ )
Otras preguntas
WILL GIVE BRAINLIEST!!! +15 POINTS!! IF YOU RESPOND WITH TE CORRECT ANSWER IN 1 MINUTE YOU GET BRAINLY!!!! A culture of 1.75x10^18 bacteria is in a petri dish A
For some reason I'm just lost
What is one way in which traditional storytelling is different from modernist stories? A. The characters in traditional stories are flawed. B. Traditional stor
Write a slope intercept for a line passing through the point (4,-3) that is paralell to the line 4x+5y=7
What strengthened the economic and political power of the chola empire?a. New religious beliefsb. Maritime trade networksc. Brilliant bodhisattva leadersd. New
Please help 15 POINTS PROBLEM BELOW
Which of the following statements is true about ions? A. Anions are positively charged ions. B. Cations are common among nonmetals. C. Charges for ions are a
What style of art was adopted as a means of spreading Christianity during the counter reformation
2x-1=3/4x +9 please help me solve
Which equation represents the following graph? A.) Y = 2/3 x + 2 B.) Y = 3/2 x + 2 C.) Y = 2/3 x – 2 D.) Y = -2/3 x + 2